2021
DOI: 10.1111/1365-2745.13541
|View full text |Cite
|
Sign up to set email alerts
|

Biological Flora of the British Isles: Crataegus laevigata

Abstract: This account presents information on all aspects of the biology of Crataegus laevigata (Poir.) DC (Midland hawthorn) (C. oxyacanthoides Thuill.) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 109 publications
(178 reference statements)
0
6
0
Order By: Relevance
“…Its sister taxon, Crataegus laevigata (cf. Thomas et al, 2021), is scarce in the suite with Quercus robur and is restricted to long-established stands. Another shrubby constant in W8 is Corylus avellana, which is rivalled by C. monogyna only in the Hedera helix and the Geranium robertianum subcommunities.…”
Section: Communitie Smentioning
confidence: 99%
See 3 more Smart Citations
“…Its sister taxon, Crataegus laevigata (cf. Thomas et al, 2021), is scarce in the suite with Quercus robur and is restricted to long-established stands. Another shrubby constant in W8 is Corylus avellana, which is rivalled by C. monogyna only in the Hedera helix and the Geranium robertianum subcommunities.…”
Section: Communitie Smentioning
confidence: 99%
“…Leaf thickness increased with irradiance too, so that leaf mass per area tended asymptotically to 10.12 mg/cm 2 (Aranda et al, 2004), leading towards significant gain in total dry weight (Grubb et al, 1996;Williams & Buxton, 1989 Aranda et al (2004) found hawthorn to be the most shade-intolerant among Ilex aquifolium, F. sylvatica, Quercus petraea, Q. pyrenaica, Prunus avium, Sorbus aria and S. aucuparia. Bradshaw (1948) noted a more tree-like habit in shaded localities compared to C. laevigata (see also Thomas et al, 2021). The Ellenberg value for light (L) is 6 (Hill et al, 1999) indicating the growth of C. monogyna in partially shaded (rarely <20% daylight) to lit places.…”
Section: Re S P On S E To B I Oti C Fac Tor Smentioning
confidence: 99%
See 2 more Smart Citations
“…Data about flowering phenology in European Crataegus species are scarce, and most studies include only C. monogyna [19], providing little detail about the length and dynamics of flowering in other Crataegus species and no data about their natural hybrids is available [10,32]. The aim of our study was to compare the flowering phenology of three sympatric Crataegus species (C. laevigata (Poir.)…”
Section: Introductionmentioning
confidence: 99%